The Influence of Knowledge, Benefit and Risk on Customer Interest in Using The BSI Qris Electronic Payment System at BSI KCP Indrapura - Sunardi, Sunardi; Siregar, Pani Akhiruddin (JURNAL EKONOMI SYARIAH, 2023)
Introduction to The Problem: The use of QR-Code is currently quite widely used for payments and is starting to gain considerable traction in Indonesia. Talking about QR Payment payments, Bank Indonesia also innovated a QR-Code-based payment system called QRIS.Purpose/Objective Study: The research aims to analyze the significant influence of knowledge, benefit and risk on customer interest in using the BSI QRIS electronic payment system at BSI KCP Indrapura.Design/Methodology/Approach: Research methods with quantitative methods described in multiple linear regression analysis models. Primary data by distributing questionnaires to respondents as a sample from August 2022 to December 2022. Sampling design with simple random sampling technique. Using the Slovin formula, the number of respondents who became a sample was 90 people for further analysis.Findings: The results of the research are as follows: (1)The estimation model shows an R2 value of 0.770 which represents the value of the coefficient of determination. This means that 77% of the dependent variable variation is able to be explained by the independent variable in this model. The remaining 23% is explained by other causes that are not included in the model; 2) The regression model on the independent variable simultaneously influences the dependent variable, so that the independent variable regression model can be used to predict the dependent variable; and (3) This research resulted in the output that there is a significant influence between the benefit on customer interest in using the BSI QRIS electronic payment system at BSI KCP Indrapura. However, it is not knowledge and risk that do not show a significant influence, so it can be concluded that the two have no relationship at all to customer interest in using the BSI QRIS electronic payment system at BSI KCP Indrapura.